An organic-solvent-tolerant esterase from thermophilic Bacillus licheniformis S-86 - Torres, Sebastián (2009)
A thermophile, halotolerant and organic-solvent-tolerant esterase producer Bacillus sp. S-86 strain previously isolated was found to belong to Bacillus licheniformis species through morphological, biochemical, 16S rRNA gene sequence analyses and rDNA intergenic spacers amplification (ITS-PCR). The strain can grow at 55 °C in presence of C2–C7 alkanols (log P = −0.86 to 2.39), and NaCl concentrations up to 15% (w/v). This bacterium showed optimal growth and esterase production at 50 °C. Two different molecular weight esterase activities were detected in zymographic assays. PMSF inhibited type I esterase activity, showing no inhibitory effect on type II esterase activity. B. licheniformis S-86 was able to grow in presence of hydroxylic organic-solvents like propan-2-ol, butan-1-ol and 3-methylbutan-1-ol. At a sub-lethal concentration of these solvents (392 mmol l−1 propan-2-ol; 99 mmol l−1 butan-1-ol, 37 mmol l−1 3-methylbutan-1-ol), adequate to produce 50% cell growth inhibition at 50 °C, an increment between 1.9 and 2.3 times was observed in type I esterase production, and between 2.2 and 3.1 times in type II esterase production.